Estudo comparativo para a implantação de processos não convencionais para corte de chapas - Alves, Henrique Eduardo (2016)
This is a comparative study of non-conventional processes for cutting plates, providing data values and equations for cost analysis aimed at the implementation of some automated systems for future business investment, facilitating investor entrepreneur vision in the best possible use of available resources in order to avoid any misleading and frustrating purchases in their companies. Being difficult to access and even bureaucratic, with these surveys deployment costs and use, it is intended to facilitate such work providing the study of easy access values. Some cutting systems plates for CNC (Computer Numeric Control) allow increased recovery time, the dimensions of the sheets to be cut, trim, etc. Therefore, a brief overview of conventional cutting systems is made, reaching the depth of operation of non conventional processes studied in order to have a better understanding of stakeholders, and which results that really does focus the study of quantification estimated costs of cutting processes Laser and Plasma.